Design and Evaluation of an AI-Driven Pipeline for Synthetic Tabular Data Generation - Sims-Handcock, Chad Calvin (Stellenbosch : Stellenbosch University, 2026)
Thesis (MEng)--Stellenbosch University, 2026.